Strategi Pemasaran Dalam Penerimaan Peserta Didik Baru - Pangestika, Rizky; Amilda, Amilda; Astuti, Mardiah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze marketing strategies in the admission of new students at SMK Negeri 3 Palembang. The type of research used by researchers is qualitative research. This research uses data sources consisting of two types, namely primary and secondary data sources. The results of this study indicate that: First, marketing strategy planning at SMK Negeri 3 Palembang is the main thing in the New Student Admission (PPDB) activity. Planning involves the principal, the vice principal of student affairs, and the school marketing team. The planning of marketing activities in PPDB at SMK Negeri 3 Palembang includes creating a committee structure, determining work programs, implementation, and evaluation. Second, at the implementation stage of marketing strategy planning, SMK Negeri 3 Palembang conducts a school promotion strategy by applying the 5 elements of the marketing mix, collaborating, and providing the best possible service to the community. Third, the evaluation of the marketing strategy at SMK Negeri 3 Palembang is carried out at the end of the PPBD implementation period in the form of an accountability report. Fourth, the problematic marketing strategy of SMK Negeri 3 Palembang in the 2022-2023 school year runs less than optimal due to the lack of enthusiasm for work motivation and teamwork of the organizing committee for new student admission activities.